(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2021)
This article analyzes the experience of teaching in scenic lighting carried out in a virtual way, exploring the “new” possibilities and the use of didactic and pedagogical tools in this teaching process. The text explores the methodological procedures and theories used by the lighting teacher, Ciel Carvalho, in the planning and execution of the course “The Movement of Light as a Co-Creating Element in Dance”. The classes were held in April 2021, through the online platform google meet, as part of the Arte Urgente creation ateliers project. In this article, the difficulties, insecurities and overcoming of virtual teaching in scenic lighting, in a course given during the Covid-19 pandemic, are reported. The text reports, through interviews and data analysis, the experience of the creative process carried out by the students and professor of the course, in which the concept of present light, by TEIXEIRA (2019) was used as a device creator of the dance/performance video dramaturgy.